UNUMDORLIGI PASTDARAJADA BO’LGAN TUPROG‘INI YAXSHILASHDA BIOKOMPOSTNING AHAMIYATI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article discusses the role of biocompost in agriculture and the national economy, its importance in ensuring environmental sustainability, as well as its re-evaluation in the modern era as the “support of the century.”